Merancang media pembelajaran digital untuk materi Bahasa Indonesia - Wan Nurul Atikah Nasution (Jurnal Komunitas Bahasa, 2023)
This study aims to determine digital learning media that can be used in learning Indonesian, as well as the design of digital learning media in learning Indonesian.Â The Digital Learning Media is designed as: Canva, Powerpoint, Quizizz, Google Form, Google Slides, Capcut, Tiktok, Wondershare Filmora. The research used in this study is qualitative research with qualitative descriptive methods which aim to develop digital learning media using computer applications, especially in Middle/High School Indonesian Language subjects. This research is expected to be able to produce educational products in the form of Digital Learning Media in improving the quality of learning. The results obtained were that 15 students used the Canva application, 12 students used Powerpoint, 7 students used the Quizizz application, 3 students used the Google Form application, 7 students used Google Slides, 6 students used the Capcut application, 3 students used the Tiktok application, 2 students using the Wondershare Filmora application with a total of 55 subjects.